2008
DOI: 10.1021/jp802255y
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Speciation in Hydrous Silica Melts. 2. Pressure Effects

Abstract: The effect of pressure on structure and water speciation in hydrated liquid silica is examined over a range of temperatures and compositions. The Feuston-Garofalini (FG) potential is used in isobaric-isothermal Monte Carlo simulations carried out at four pressures (0.25, 1.0, 2.5, and 10 GPa) for seven temperatures (2000 < or = T < or= 9000 K) and five compositions (0.0 < or = x_w < or = 0.4). The FG potential yields a stable melt phase for p > or = 1.0 GPa and/or x_w < or = 0.1 for all temperatures. The volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…17 This paper will proceed as follows: in section 2, we will provide the methodological details of the study; in section 3, an analysis of the simulations; and in section 4, a summary of these findings. In the companion to this paper, 18 pressure effects on hydrated silica are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…17 This paper will proceed as follows: in section 2, we will provide the methodological details of the study; in section 3, an analysis of the simulations; and in section 4, a summary of these findings. In the companion to this paper, 18 pressure effects on hydrated silica are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Can hydrous silica liquid be a potential proton conductor? A first-principles approach [13-15] correctly describing hydrogen bond, which is an issue in widely used (dominantly) ionic models [16], can answer these questions.Here, we use the first-principles molecular dynamics method [17] to investigate the structure and dynamics of hydrous (with 8.25 wt% water) and anhydrous silica liquids as a function of pressure (P) and temperature (T) and evaluate or isolate the effects of water unlike in the case of other silicates (e.g., MgSiO 3 ) that are already depolymerized due to other cations. The local density approximation [18] and projector augmented wave method [19] (with a cutoff of 450 eV and gamma point) were used.…”
mentioning
confidence: 99%
“…Can hydrous silica liquid be a potential proton conductor? A first-principles approach [13][14][15] correctly describing hydrogen bond, which is an issue in widely used (dominantly) ionic models [16], can answer these questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of isochemical compaction with increasing pressure, FPMD simulations [ Anderson et al ., ; Mookherjee et al ., ; Karki and Stixrude , ; Karki et al ., ] and in situ structural observations [ Yamada et al ., ] have shown that bond lengths of O–H and Si–O increase monotonously with increasing pressure. The coordination of Si–O, O–H, and H–O also increases with increasing pressure.…”
Section: Resultsmentioning
confidence: 98%